A method for preparing carboxymethyl cellulose / chitosan shape memory film

By using the carboxymethyl cellulose and chitosan to prepare a forms of memory film, the problem of cumbersome and biocompatibility in the existing technologies has been solved, and the film preparation of high mechanical performance and water response shape memory performance is realized. It is suitable for The field of biology and medicine.

CN116003842BActive Publication Date: 2025-01-28GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211650866.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-01-28
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The preparation process of existing shape memory membranes is complicated, poor biocompatibility, and non-biodegradability, which limits its application in the fields of biology, medicine, etc.

Method used

The carboxymethyl cellulose and chitosan are used as the raw material. The solution aggregation method is used to prepare the carboxymethyl cellulose/shell polycanic memory film to improve its mechanical stability and water reaction shape memory performance.

Benefits of technology

Effectively improve the mechanical properties and stability of the membrane, gives them water -to -shape memory performance, improve biocompatibility, realize the high value -added utilization of biomass resources, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116003842B_ABST
    Figure CN116003842B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a carboxymethyl cellulose / chitosan shape memory membrane, comprising the following steps: (a) preparing a carboxymethyl cellulose gel product: (b1) preparing a dispersion of 4-7 mg / ml of carboxymethyl cellulose and deionized water to obtain a carboxymethyl cellulose aqueous solution; (b2) preparing a chitosan / acetic acid solution with a mass fraction of 2%-5%; (b3) adding the carboxymethyl cellulose aqueous solution obtained in step (1) to the chitosan / acetic acid solution with a mass fraction of 2%-5% to obtain a carboxymethyl cellulose / chitosan mixed solution with a mass fraction of 0.5-4.0wt%; (b4) subjecting the mixed solution to a film-forming treatment by suction filtration to obtain a carboxymethyl cellulose / chitosan shape memory hydrogel, and drying the hydrogel in a drying oven at 25-30°C for 5-6 hours, then heating the mixture to 35-50°C for drying for 24-36 hours to allow the water to slowly and completely evaporate, thereby obtaining a carboxymethyl cellulose / chitosan shape memory membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material synthesis, and particularly relates to a method for preparing a carboxymethyl cellulose / chitosan shape memory film. Background Art

[0002] Shape memory materials are one of the new smart materials, which can be divided into three categories: shape memory ceramics, shape memory alloys and shape memory polymers (SMP); among them, SMP has the widest application, good biocompatibility, can remember one or more temporary shapes, and has the ability to recover from a temporary deformation state to its initial shape under the stimulation of external conditions, and undergoes a shape memory cycle of "initial deformation-temporary deformation-initial deformation". At present, the memory performance of SMP can be triggered by a variety of stimulation methods, such as temperature, light, electricity, magnetism, pH value and water response, which can directly or indirectly drive the shape memory effect of polymers. SMP has adjustable mechanical properties in a wide range, and it also has the advantages of large deformation, easy molding, light weight and low price. Some SMPs are biodegradable, showing environmental friendliness and conforming to the concept of environmental protection. It has great application value in aerospace, smart fabrics, biomedicine, electronic components and automatic control systems, and provides new ideas for the development of smart stimulus-responsive materials.

[0003] The emergence of intelligent stimulus-responsive materials has not only effectively liberated labor productivity, but also brought great convenience and comfort to human life. Shape memory membrane is one of the intelligent stimulus-responsive materials. Research on its keen stimulus responsiveness and excellent bionic properties has become a hot topic in the current high-tech field. However, the preparation process of traditional shape memory membranes is relatively cumbersome. For example, although materials such as polyurethane, polyester and polyolefins show good shape memory effects, they still have shortcomings such as poor biocompatibility and non-biodegradability, which do not conform to the concept of environmental protection, resulting in limited application in biology, medicine and other fields. Therefore, it is of great significance to develop natural polymer-based shape memory materials.

[0004] Chitosan (CS) is the only alkaline polysaccharide among natural polysaccharides. It is generally insoluble in water and conventional organic solvents. However, due to its -NH2 group, it is very easy to react with acid to form salts. Therefore, it can be dissolved in dilute acids such as hydrochloric acid, formic acid, acetic acid, and lactic acid. There are a large number of -NH2 and -OH groups on the chitosan molecular chain. This structure gives chitosan the advantages of adhesion, anticoagulation, excellent biocompatibility, natural antibacterial properties, and biodegradability. At the same time, it is easy to form a film, so that chitosan has been widely used in medical, biological, environmental protection and other fields. However, the mechanical strength of chitosan film is low and its toughness is poor; and it contains more hydroxyl and amino groups, which makes it easy to absorb water and is not convenient for long-term storage and use; it is corroded in an acidic environment, which greatly reduces the stability of its mechanical properties and structure, resulting in limitations in practical applications. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a carboxymethyl cellulose / chitosan shape memory membrane. The method uses chitosan as a matrix and carboxymethyl cellulose as a reinforcing material to synthesize a carboxymethyl cellulose / chitosan shape memory membrane, which can not only effectively improve the mechanical stability of the chitosan membrane, but also give the chitosan membrane a water-responsive shape memory property, and realize high value-added utilization of biomass resources, effectively improve the biocompatibility of the shape memory membrane, ensure resource safety, and reduce environmental pollution.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a carboxymethyl cellulose / chitosan shape memory membrane, comprising the following steps:

[0007] (a) Preparation of carboxymethyl cellulose gel product:

[0008] (a1) adding 30-50 mL of 10 wt% NaOH solution and 4-7 g of cellulose microcrystals into a reactor, and then adding 80-180 mL of anhydrous ethanol, and stirring for 0.3-0.7 h;

[0009] (a2) adding 2.5-3.5 g of chloroacetic acid to the above reactor, heating to 65-85° C. and reacting for 4-6 h;

[0010] (a3) After the reaction is completed, the product is filtered, washed, and centrifuged to obtain a carboxymethyl cellulose gel product;

[0011] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0012] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0013] (b1) preparing a 4-7 mg / ml dispersion of carboxymethyl cellulose and deionized water to obtain a carboxymethyl cellulose aqueous solution;

[0014] (b2) preparing an aqueous solution of acetic acid with a mass fraction of 2% to 4%, and weighing 0.3 g to 0.5 g of chitosan to prepare a chitosan / acetic acid solution with a mass fraction of 2% to 5%;

[0015] (b3) adding the carboxymethyl cellulose aqueous solution to a chitosan / acetic acid solution having a mass fraction of 2% to 5%, and ultrasonically dispersing the solution for 20 to 45 minutes to obtain a carboxymethyl cellulose / chitosan mixed solution having a mass fraction of 0.5 to 4.0 wt %;

[0016] (b4) The mixed solution is filtered and film-formed until no water droplets are dropped within 10 to 20 minutes to obtain a carboxymethyl cellulose / chitosan shape memory hydrogel, and the hydrogel is placed in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is increased to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a carboxymethyl cellulose / chitosan shape memory membrane.

[0017] Further, in step (a3), the filtered product is repeatedly washed with distilled water until it becomes neutral. The main purpose is to remove unreacted chloroacetic acid and sodium hydroxide solution, ensure the purity of the product carboxymethyl cellulose gel, and ensure that when the product is subjected to infrared testing, the absorption peaks of the groups are all attributed to the absorption of the groups on the product.

[0018] Furthermore, in step (a4), the product after rotary evaporation is placed in a freeze dryer at a temperature of -55 to -35°C and a vacuum degree of 12 to 20 Pa for freezing treatment for 24 to 30 hours.

[0019] Furthermore, in step (b2), the chitosan / acetic acid solution is prepared by adding 0.3-0.5 g of chitosan powder to 8-12 mL of 2%-4% acetic acid solution, stirring at a speed of 300-450 r / min for 1-1.5 h to obtain a chitosan / acetic acid solution with a mass fraction of 2%-5%.

[0020] Furthermore, in step (b3), the preparation method of the carboxymethyl cellulose / chitosan mixed solution is as follows: 4-7 mg / ml carboxymethyl cellulose aqueous solution and 2%-5% chitosan / acetic acid solution are dispersed by an ultrasonic cleaning machine at a power of 300 W for 20-45 min to obtain a 0.5-4.0 wt % carboxymethyl cellulose / chitosan mixed solution.

[0021] Furthermore, in step (b4), the mixed solution is filtered using a sand core filter until no water droplets fall within 10 to 20 minutes and then dried.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention uses carboxymethyl cellulose and chitosan as raw materials and utilizes a solution polymerization method to prepare a carboxymethyl cellulose / chitosan film (CMC / CS) with water-responsive shape memory properties. Cellulose is rich in active groups and can generate hydrogen bonds with chitosan to improve compatibility. Cellulose with high stability and mechanical properties is distributed in the composite system, thereby improving the mechanical properties and stability of the cellulose / chitosan shape memory film. The preparation method has the characteristics of simple operation, greenness, environmental protection and pollution-free.

[0024] 2. The carboxymethyl cellulose / chitosan shape memory membrane prepared by the present invention realizes high value-added utilization of biomass resources, can effectively improve the biocompatibility of the shape memory membrane, ensure resource safety, and reduce environmental pollution.

[0025] 3. The carboxymethyl cellulose / chitosan shape memory film prepared by the present invention provides a theoretical basis for the application expansion of the material and broadens the application field of the shape memory composite film material.

[0026] 4. The carboxymethyl cellulose / chitosan shape memory membrane prepared by the present invention uses chloroacetic acid to modify cellulose, so that the modified cellulose has more active sites to undergo hydrogen bond cross-linking reaction with chitosan, thereby giving the carboxymethyl cellulose / chitosan shape memory membrane hydrogen bond rupture in the presence of water, showing water stimulus responsiveness BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The infrared spectra of CMC, CS and CMC / CS memory films with different carboxymethyl cellulose contents are shown in Figure (a). Figure (b) is a comparison of infrared spectra of CMC, CS and 2.5wt%-CMC / CS memory films. The infrared spectra of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5 are shown in Figure (a).

[0028] Figure 2 DSC curves of CMC, CS and CMC / CS memory films with different carboxymethyl cellulose contents; wherein, Figure (a) is a DSC curve of CMC, CS and 2.5wt%-CMC / CS memory films; Figure (b) is a DSC temperature rise curve of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5;

[0029] Figure 3The stress-strain curves of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5;

[0030] Figure 4 Schematic diagram of the shape recovery process of 3wt%-CMC / CS memory film in water. DETAILED DESCRIPTION

[0031] The method of the present invention is described in detail below in conjunction with specific embodiments. The carboxymethyl cellulose / chitosan shape memory film of the present invention can be abbreviated as CMC / CS memory film, and the final product of the present invention is subjected to a series of characterizations, such as infrared, TG and DSC. Carboxymethyl cellulose can be abbreviated as CMC, and chitosan can be abbreviated as CS.

[0032] 1. Preparation of carboxymethyl cellulose / chitosan shape memory membrane

[0033] Example 1

[0034] A method for preparing a carboxymethyl cellulose / chitosan shape memory film comprises the following steps:

[0035] (a) Preparation of carboxymethyl cellulose gel product:

[0036] (a1) adding 40 mL of 10 wt% NaOH solution and 6 g of cellulose microcrystals into a three-necked round-bottom flask in a reactor, and then adding 100 mL of anhydrous ethanol, and stirring with an electric stirrer for 0.5 h;

[0037] (a2) Add 3 g of chloroacetic acid to the above flask, heat it to 70°C, and react with an electric stirrer under mechanical stirring for 4 hours;

[0038] (a3) After the reaction is completed, the product is filtered and repeatedly washed with distilled water until the pH value of the crude product reaches a neutral value, and the neutral solution is centrifuged using a high-speed centrifuge to obtain a carboxymethyl cellulose gel product;

[0039] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0040] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0041] (b1) weighing 20 ml of a 5 mg / ml aqueous solution of carboxymethyl cellulose;

[0042] (b2) First, 0.3 g of chitosan powder was added to 9.7 mL of 2% acetic acid solution, and the mixture was stirred at 350 r / min for 1 h to obtain a chitosan / acetic acid solution with a mass fraction of 3%;

[0043] (b3) adding 3% chitosan / acetic acid solution to the above carboxymethyl cellulose aqueous solution, and dispersing by ultrasonic for 30 minutes to obtain a 1.0 wt% carboxymethyl cellulose / chitosan mixed solution, i.e., a 1.0 wt%-CMC / CS mixed solution;

[0044] (b4) The mixed solution is filtered and film-formed until no water droplets fall within 10 to 20 minutes to obtain a 1.0 wt%-CMC / CS shape memory hydrogel. The hydrogel is dried in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is raised to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a 1.0 wt%-CMC / CS shape memory membrane.

[0045] Example 2

[0046] A method for preparing a carboxymethyl cellulose / chitosan shape memory film comprises the following steps:

[0047] (a) Preparation of carboxymethyl cellulose gel product:

[0048] (a1) adding 40 mL of 10 wt% NaOH solution and 6 g of cellulose microcrystals into a three-necked round-bottom flask in a reactor, and then adding 100 mL of anhydrous ethanol, and stirring with an electric stirrer for 0.5 h;

[0049] (a2) Add 3 g of chloroacetic acid to the above flask, heat it to 70°C, and react with an electric stirrer under mechanical stirring for 4 hours;

[0050] (a3) After the reaction is completed, the product is filtered and repeatedly washed with distilled water until the pH value of the crude product reaches a neutral value, and the neutral solution is centrifuged using a high-speed centrifuge to obtain a carboxymethyl cellulose gel product;

[0051] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0052] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0053] (b1) weighing 30 ml of a 5 mg / ml aqueous solution of carboxymethyl cellulose;

[0054] (b2) First, 0.3 g of chitosan powder was added to 9.7 mL of 2% acetic acid solution, and the mixture was stirred at 350 r / min for 1 h to obtain a chitosan / acetic acid solution with a mass fraction of 3%;

[0055] (b3) adding 3% chitosan / acetic acid solution to the above carboxymethyl cellulose aqueous solution, and dispersing by ultrasonic for 30 minutes to obtain a 1.5wt% carboxymethyl cellulose / chitosan mixed solution, i.e., a 1.5wt%-CMC / CS mixed solution;

[0056] (b4) The mixed solution is filtered and film-formed until no water droplets fall within 10 to 20 minutes to obtain a 1.5 wt%-CMC / CS shape memory hydrogel. The hydrogel is dried in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is raised to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a 1.5 wt%-CMC / CS shape memory membrane.

[0057] Example 3

[0058] A method for preparing a carboxymethyl cellulose / chitosan shape memory film comprises the following steps:

[0059] (a) Preparation of carboxymethyl cellulose gel product:

[0060] (a1) adding 40 mL of 10 wt% NaOH solution and 6 g of cellulose microcrystals into a three-necked round-bottom flask in a reactor, and then adding 100 mL of anhydrous ethanol, and stirring with an electric stirrer for 0.5 h;

[0061] (a2) Add 3 g of chloroacetic acid to the above flask, heat it to 70°C, and react with an electric stirrer under mechanical stirring for 4 hours;

[0062] (a3) After the reaction is completed, the product is filtered and repeatedly washed with distilled water until the pH value of the crude product reaches a neutral value, and the neutral solution is centrifuged using a high-speed centrifuge to obtain a carboxymethyl cellulose gel product;

[0063] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0064] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0065] (b1) weighing 41 ml of a 5 mg / ml aqueous solution of carboxymethyl cellulose;

[0066] (b2) First, 0.3 g of chitosan powder was added to 9.7 mL of 2% acetic acid solution, and the mixture was stirred at 350 r / min for 1 h to obtain a chitosan / acetic acid solution with a mass fraction of 3%;

[0067] (b3) adding 3% chitosan / acetic acid solution to the above carboxymethyl cellulose aqueous solution, and dispersing by ultrasonic for 30 minutes to obtain a 2.0wt% carboxymethyl cellulose / chitosan mixed solution, i.e., a 2.0wt%-CMC / CS mixed solution;

[0068] (b4) The mixed solution is filtered and film-formed until no water droplets fall within 10 to 20 minutes to obtain a 2.0 wt%-CMC / CS shape memory hydrogel. The hydrogel is dried in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is raised to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a 2.0 wt%-CMC / CS shape memory membrane.

[0069] Example 4

[0070] A method for preparing a carboxymethyl cellulose / chitosan shape memory film comprises the following steps:

[0071] (a) Preparation of carboxymethyl cellulose gel product:

[0072] (a1) adding 40 mL of 10 wt% NaOH solution and 6 g of cellulose microcrystals into a three-necked round-bottom flask in a reactor, and then adding 100 mL of anhydrous ethanol, and stirring with an electric stirrer for 0.5 h;

[0073] (a2) Add 3 g of chloroacetic acid to the above flask, heat it to 70°C, and react with an electric stirrer under mechanical stirring for 4 hours;

[0074] (a3) After the reaction is completed, the product is filtered and repeatedly washed with distilled water until the pH value of the crude product reaches a neutral value, and the neutral solution is centrifuged using a high-speed centrifuge to obtain a carboxymethyl cellulose gel product;

[0075] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0076] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0077] (b1) weighing 51 ml of a 5 mg / ml aqueous solution of carboxymethyl cellulose;

[0078] (b2) First, 0.3 g of chitosan powder was added to 9.7 mL of 2% acetic acid solution, and the mixture was stirred at 350 r / min for 1 h to obtain a chitosan / acetic acid solution with a mass fraction of 3%;

[0079] (b3) adding 3% chitosan / acetic acid solution to the above carboxymethyl cellulose aqueous solution, and dispersing by ultrasonic for 30 minutes to obtain a 2.5wt% carboxymethyl cellulose / chitosan mixed solution, i.e., a 2.5wt%-CMC / CS mixed solution;

[0080] (b4) The mixed solution is filtered and film-formed until no water droplets fall within 10 to 20 minutes to obtain a 2.5 wt%-CMC / CS shape memory hydrogel. The hydrogel is dried in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is raised to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a 2.5 wt%-CMC / CS shape memory membrane.

[0081] Example 5

[0082] A method for preparing a carboxymethyl cellulose / chitosan shape memory film comprises the following steps:

[0083] (a) Preparation of carboxymethyl cellulose gel product:

[0084] (a1) adding 40 mL of 10 wt% NaOH solution and 6 g of cellulose microcrystals into a three-necked round-bottom flask in a reactor, and then adding 100 mL of anhydrous ethanol, and stirring with an electric stirrer for 0.5 h;

[0085] (a2) Add 3 g of chloroacetic acid to the above flask, heat it to 70°C, and react with an electric stirrer under mechanical stirring for 4 hours;

[0086] (a3) After the reaction is completed, the product is filtered and repeatedly washed with distilled water until the pH value of the crude product reaches a neutral value, and the neutral solution is centrifuged using a high-speed centrifuge to obtain a carboxymethyl cellulose gel product;

[0087] (a4) subjecting the carboxymethyl cellulose gel product obtained in step (3) to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose;

[0088] (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane:

[0089] (b1) weighing 62 ml of a 5 mg / ml aqueous solution of carboxymethyl cellulose;

[0090] (b2) First, 0.3 g of chitosan powder was added to 9.7 mL of 2% acetic acid solution, and the mixture was stirred at 350 r / min for 1 h to obtain a chitosan / acetic acid solution with a mass fraction of 3%;

[0091] (b3) adding 3% chitosan / acetic acid solution to the above carboxymethyl cellulose aqueous solution, and dispersing by ultrasonic for 30 minutes to obtain a 3.0wt% carboxymethyl cellulose / chitosan mixed solution, i.e., a 3.0wt%-CMC / CS mixed solution;

[0092] (b4) The mixed solution is filtered and film-formed until no water droplets fall within 10 to 20 minutes to obtain a 3.0 wt%-CMC / CS shape memory hydrogel. The hydrogel is dried in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is raised to 35 to 40° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a 3.0 wt%-CMC / CS shape memory membrane.

[0093] 2. Performance test of carboxymethyl cellulose / chitosan shape memory membrane prepared by the present invention

[0094] 1. Infrared test (FT-IR) analysis

[0095] Figure 1 The infrared spectra of CMC, CS and CMC / CS memory films with different carboxymethyl cellulose contents are shown in Figure 2. Figure 1 (a) is a comparison of the infrared spectra of CMC, CS and 2.5wt%-CMC / CS. It can be seen from the figure that the peak shapes of CMC and CS samples are very similar, because they have similar molecular structures. The characteristic absorption wave number of cellulose molecules is 3392cm -1 is the stretching vibration absorption peak of OH, 2880cm -1 is the stretching vibration absorption peak of CH, 1629cm -1 is the stretching vibration absorption peak of C=O, 1141cm -1 The absorption peaks correspond to the vibration absorption peaks of -COC and OH. Figure 1 The CS curve in (a) shows that at 3446 cm -1 The peak at 1592 cm is attributed to the stretching vibration absorption peaks of NH and OH in chitosan. -1 is the absorption peak of amino group in chitosan; Figure 1 From the 2.5wt%-CMC / CS curve in (a), it can be seen that after the reaction, the -1 The peak at 1636cm becomes sharper and the intensity increases. -1 There are obvious stretching vibration peaks of amide groups, which preliminarily proves the synthesis of 2.5wt%-CMC / CS shape memory film.

[0096] Figure (b) is a comparison of infrared spectra of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5. There are four main characteristic peaks in the figure, which are 3334cm -1 -OH stretching vibration absorption peak, 2888cm -1 Symmetrical and asymmetric -CH- stretching vibration absorption peaks, 1636cm -1 1557cm -1 The peaks at 3334 cm represent the stretching vibration peak of the C=O amide group and the bending vibration absorption peak of NH. -1 The overlapping absorption peaks of OH stretching vibration and NH stretching vibration at the CMC / CS memory film shifted to varying degrees. This is attributed to the large number of hydrogen bonds between the chitosan and carboxymethyl cellulose molecular chains, which led to the shift of the stretching vibration peaks of OH and NH in the CMC / CS memory film.

[0097] 2. Differential Scanning Calorimetry (DSC) Test Analysis

[0098] Figure 2 Figure 3 is the DSC curve of CMC, CS and CMC / CS memory membranes with different carboxymethyl cellulose contents; Figure (a) is the DSC curve of CMC, CS and 2.5wt%-CMC / CS memory membranes. It can be seen from the figure that the glass transition temperatures of the three curves of CMC, CS and 2.5wt%-CMC / CS are not much different. The main reason is that chitosan and cellulose have similar polysaccharide structures, and both are biomass materials with good biocompatibility and degradability. Figure (b) is a DSC temperature rise curve of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5. It can be seen from the figure that the glass transition temperatures (Tg) of 1.0wt%-CMC / CS, 1.5wt%-CMC / CS, 2.0wt%-CMC / CS, 2.5wt%-CMC / CS, and 3.0wt%-CMC / CS are 18.5°C, 18.8°C, 18.7°C, 18.9°C, and 19.5°C, respectively. The Tg of the CMC / CS memory film gradually increases with the increase of the carboxymethyl cellulose content. The reason may be that the hydrogen bonding and cross-linking degree of the CMC / CS memory film increase, resulting in a decrease in the free volume of the polymer chain, a compact structure, and a slight increase in the glass transition temperature.

[0099] 3. Mechanical properties analysis

[0100] Figure 3The stress-strain curves of CMC / CS memory films with different carboxymethyl cellulose contents prepared in Examples 1-5 show that the tensile strengths of 1.0wt%-CMC / CS and 1.5wt%-CMC / CS are 76MPa and 84MPa, respectively, while the tensile strengths of 2.0wt%-CMC / CS, 2.5wt%-CMC / CS and 3.0wt%-CMC / CS decrease with the increase of carboxymethyl cellulose content, but their elongation at break gradually increases, and the toughness of the memory film gradually improves. The main reason is that carboxymethyl cellulose has a higher degree of crystallinity and good toughness, and with the increase of carboxymethyl cellulose content, more intermolecular hydrogen bonds are formed between the two, thereby improving the mechanical properties of the chitosan film.

[0101] 4. Characterization of water-responsive shape memory performance

[0102] The test of the water-responsive shape memory performance of the CMC / CS memory film takes the 3.0wt%-CMC / CS memory film as an example. Memory films with other proportions also have faster water-responsive shape memory performance. Figure 4 This is a diagram of the shape recovery process of the 3wt%-CMC / CS memory film in water. By bending it in half, fixing its temporary shape at room temperature, and then putting it into water, the shape recovery process of the memory film in water is recorded by a camera. Taking the 3.0wt%-CMC / CS memory film as an example, it can be seen from the figure that the 3.0wt%-CMC / CS memory film is cut into a rectangle with a length of about 45mm. After folding it in half (see Figure (b)), the length is about 23mm. There is no obvious recovery of the bent shape in the air. Then it is transferred to a water environment at room temperature. After being immersed in water for 6s (see Figure (e)), it has obvious recovery. When immersed in water for 11s (see Figure (f)), the recovery is more obvious. When immersed in water for 18s (see Figure (g)), the film has completely and quickly recovered to a linear state. At the end of the test (see Figure (h)), the length is 45mm. It can be found that the recovery rate is fast and the recovery time is short. It can be concluded that the 3.0wt%-CMC / CS memory film has an adjustable bending-unfolding water-responsive shape memory effect. In the initial stage, due to the large deformation, the recovery rate of the 3.0wt%-CMC / CS memory film is also large, and then the deformation recovery slows down. The above results show that the 3.0wt%-CMC / CS memory film has good water-responsive shape memory material properties. The deformation of the 3.0wt%-CMC / CS memory film is mainly due to the strong intermolecular hydrogen bonding force between carboxymethyl cellulose and chitosan. When there is no water stimulation, the temporary shape is mainly fixed by hydrogen bonding. When in water, when water molecules enter the memory film, the strong hydrogen bonds formed by carboxymethyl cellulose and chitosan are broken, and the force formed with water molecules is small, so the temporary shape of the memory film is restored to the initial length.

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a carboxymethyl cellulose / chitosan shape memory membrane, characterized in that: The steps include: (a) Preparation of carboxymethyl cellulose gel product: (a1) adding 30-50 mL of 10 wt% NaOH solution and 4-7 g of cellulose microcrystals into a reactor, and then adding 80-180 mL of anhydrous ethanol, and stirring for 0.3-0.7 h; (a2) adding 2.5-3.5 g of chloroacetic acid to the above reactor, heating to 65-85° C. and reacting for 4-6 h; (a3) After the reaction is completed, the product is filtered, washed, and centrifuged to obtain a carboxymethyl cellulose gel product; (a4) subjecting the carboxymethyl cellulose gel product obtained in step (a3) ​​to rotary evaporation and freeze drying to obtain dry carboxymethyl cellulose; (b) Preparation of carboxymethyl cellulose / chitosan shape memory membrane: (b1) preparing a 4-7 mg / mL dispersion of carboxymethyl cellulose and deionized water to obtain a carboxymethyl cellulose aqueous solution; (b2) preparing an aqueous solution of acetic acid with a mass fraction of 2% to 4%, and weighing 0.3 g to 0.5 g of chitosan to prepare a chitosan / acetic acid solution with a mass fraction of 2% to 5%; (b3) adding the carboxymethyl cellulose aqueous solution obtained in step (b1) to a chitosan / acetic acid solution having a mass fraction of 2% to 5%, and ultrasonically dispersing for 20 to 45 minutes to obtain a carboxymethyl cellulose / chitosan mixed solution having a mass fraction of 0.5 to 4.0 wt %; (b4) The mixed solution is filtered and film-formed until no water droplets are dropped within 10 to 20 minutes to obtain a carboxymethyl cellulose / chitosan shape memory hydrogel, and the hydrogel is placed in a drying oven at 25 to 30° C. for 5 to 6 hours, and then the temperature is increased to 35 to 50° C. and dried for 24 to 36 hours to allow the water to slowly and completely evaporate, thereby obtaining a carboxymethyl cellulose / chitosan shape memory membrane.

2. The method for preparing the carboxymethyl cellulose / chitosan shape memory membrane according to claim 1, characterized in that: In step (a3), the filtered product is repeatedly washed with distilled water until it becomes neutral.

3. The method for preparing the carboxymethyl cellulose / chitosan shape memory membrane according to claim 1, characterized in that: In step (a4), the product after rotary evaporation is placed in a freeze dryer at a temperature of -55 to -35°C and a vacuum degree of 12 to 20 Pa for freezing treatment for 24 to 30 hours.

4. The method for preparing the carboxymethyl cellulose / chitosan shape memory membrane according to claim 1, characterized in that: In step (b2), the chitosan / acetic acid solution is prepared by adding 0.3 g to 0.5 g of chitosan to 8 to 12 mL of 2 to 4% acetic acid aqueous solution, stirring at a speed of 300 to 450 r / min for 1 to 1.5 hours to obtain a chitosan / acetic acid solution.

5. The method for preparing the carboxymethyl cellulose / chitosan shape memory membrane according to claim 1, characterized in that: In step (b3), the preparation method of the carboxymethyl cellulose / chitosan mixed solution is as follows: 4-7 mg / mL carboxymethyl cellulose aqueous solution and 2%-5% chitosan / acetic acid solution are dispersed by an ultrasonic cleaning machine at a power of 300 W for 20-45 min to obtain a 0.5-4.0 wt% carboxymethyl cellulose / chitosan mixed solution.

6. The method for preparing the carboxymethyl cellulose / chitosan shape memory membrane according to claim 1, characterized in that: In step (b4), the mixed solution is filtered using a sand core filter until no water droplets fall within 10 to 20 minutes and then dried.

Citation Information

Patent Citations

  • Preparation method of high-strength water-response cellulose-based shape memory composite material

    CN108467517A

  • Hemicellulose / chitosan based compound membrane with high flexibility and mechanical strength and preparation method thereof

    CN109942847A